The signs of sin : seriousness of offence in biblical law - Burnside, Jonathan P. (Jonathan Patrick) (Journal for the study of the Old Testament. Supplement series ;, 2003)
What makes one crime more serious than another, and why? This book investigates the problem of "seriousness of offence" in English law from the comparative perspective of biblical law. Burnside takes a semiotic approach to show how biblical conceptions of seriousness are synthesised and communicated through various descriptive and performative registers. Seven case studies show that biblical law discriminates between the seriousness of different offences and between the relative seriousness of the same offence when committed by different people or when performed in different ways. Re.